High figure of merit of the post-annealed Ti/Al/ITO transparent conductive contacts sputter deposited on n-GaN - Ali, A.H.; Hassan, Z.; Shuhaimi, A. (Elsevier, 2016)
This paper reports on the enhanced electrical and optical characteristics of Ti/Al/ITO transparent conductive contacts (TCC) deposited on n-GaN for light emitting device applications. Ti/Al thin metal layer was inserted under the top ITO transparent conductive oxides (TCO) in order to improve the electrical characteristics of the TCC. The TCC multi-layer was deposited on n-GaN by magnetron sputtering system in room temperature. Post-annealing treatment was conducted on the TCC after the deposition process at 600 °C for 15 min. TCC sample analysis was conducted in order to determine the structural, morphological, electrical and optical characteristics of the samples. The post-annealed sample shows improved crystalline structure with smoother surface morphological of TCC. The electrical resistivity and optical transmittance of the post-annealed sample improved significantly as compared to the as-deposited samples. The measured electrical resistivity and optical transmittance of the post-annealed sample is 8.607 × 10−5Ω-cm and 95%, respectively resulted in high figure of merit of 5.91 × 10−2Ω−1.